All in the family: parental substance misuse, harsh parenting, and youth substance misuse among juvenile justice-involved youth. (August 2021) - Bosk, Emily Adlin; Anthony, Wen Li; Folk, Johanna Bailey; Williams-Butler, Abigail
Highlights: Parent substance misuse and mental health predict youth substance misuse. Experiences with harsh parenting are common among justice-involved youth. Black youth experience fewer types of harsh parenting compared to White youth. Harsh parenting mediates the link between parent and youth substance misuse. Abstract: Purpose: Research consistently connects parental and youth substance misuse, yet less is known about the mechanisms driving this association among justice-involved youth. We examine whether harsh parenting is an explanatory mechanism for the association between parental substance use and parental mental health and youth substance use disorder in a sample of justice-involved youth. Methods: Data were drawn from the Northwestern Juvenile Project, a large-scale longitudinal survey of mental health and substance misuse in a representative sample of youth in juvenile detention. Harsh parenting, child maltreatment, youth alcohol and cannabis use disorder, and parental substance misuse and mental health were assessed among 1, 825 detained youth (35.95% female) at baseline, three-year follow-up, and four-year follow-up. Results: At baseline, over 80% of youth used alcohol and/or cannabis; at the four-year follow-up, 16.35% and 19.69% of the youth were diagnosed with alcohol and cannabis use disorder, respectively. More than 20% of youth reported their parent misused substances and 6.11% reported a parent had a severe mental health need. Black youth experienced significantly fewer types of harsh parenting compared to White youth. Multivariate path analyses revealed harsh parenting mediated the association between parental substance misuse and mental health on youth alcohol and cannabis use disorder. Harsh parenting that does not rise to the level of child maltreatment mediated the association between parental substance misuse and mental health on youth alcohol use disorder; in contrast, child maltreatment did not mediate these associations. Multigroup analyses revealed the effect of harsh parenting on youth alcohol and cannabis use disorder did not vary across sex or race-ethnic subgroups. Conclusions: Harsh parenting represents one mechanism for the intergenerational continuity of alcohol and cannabis misuse and should be regularly assessed for and addressed in juvenile justice settings.